Skin ageing increasing in menopausal period - Rotsztejn, Helena (Menopause Review/Przegląd Menopauzalny, 2004)
The symptoms of skin ageing such wrinkles, increased dryness, loss of elasticity increase in menopausal women. Hormonal replacement therapy can positive influence on the skin conditions.